FEATURES OF THE FORMATION OF THE ABILITY TO WORK WITH THE BALL BASED ON VISUALMOTOR AND REACTIVE COORDINATION - Khaydarov Bohodirjon Yursinboyevich (Bright Mind Publishing, 2025)
This study examined the initial indicators of hand-eye coordination and ball-handling skills among 11–13-year-old girls studying in grades 5–7. The analysis revealed a consistent development of reactive and visuomotor coordination with increasing age. Based on the Student’s t-test, statistical significance (P<0.05) was determined, with notable differences observed between the 6th and 7th grades. The findings confirm the importance of regular training sessions in developing coordination abilities among schoolgirls.
Keywords: Hand-eye coordination, reactive coordination, visuomotor coordination, schoolgirls, ball handling, physical development.